2023
DOI: 10.7150/ijbs.85656
|View full text |Cite
|
Sign up to set email alerts
|

CENPA functions as a transcriptional regulator to promote hepatocellular carcinoma progression via cooperating with YY1

Jingyu Liao,
Zeyu Chen,
Ruizhi Chang
et al.

Abstract: The centromere proteins (CENPs), a critical mitosis-related protein complexes, are involved in the kinetochore assembly and chromosome segregation. In this study, we identified that CENPA was significantly up-regulated in HCC and highly expressed CENPA correlated with poor prognosis for HCC patients. Knockdown of CENPA inhibited HCC cell proliferation and tumor growth in vitro and in vivo . Mechanistically, CENPA transcriptionally activated and cooperated with YY1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Further details of the role of Nrp2 in cancer have been described in other malignancies [ 91 , 100 , 101 , 102 , 103 , 104 ]. Nrp2 enhances cancer cell survival through the regulation of autophagy and endocytic trafficking, a function distinct from its role as a co-receptor [ 105 ].…”
Section: Neuropilin-2 In Benign and Malignant Lung Processesmentioning
confidence: 99%
“…Further details of the role of Nrp2 in cancer have been described in other malignancies [ 91 , 100 , 101 , 102 , 103 , 104 ]. Nrp2 enhances cancer cell survival through the regulation of autophagy and endocytic trafficking, a function distinct from its role as a co-receptor [ 105 ].…”
Section: Neuropilin-2 In Benign and Malignant Lung Processesmentioning
confidence: 99%
“…Liao and colleagues discovered that CENPA was markedly increased in HCC, and its high expression was associated with a worse prognosis in HCC patients. CENPA was shown to be lactylated at lysine 124 (K124) [128]. Chen showed that MRE11, an important protein involved in homologous recombination (HR), is modified by lactylation at K673 by the CBP acetyltransferase in reaction to DNA damage, and this process relies on ATM phosphorylation [129].…”
Section: Modification Sites Of Lactylationmentioning
confidence: 99%